The Obama effect : multidisciplinary renderings of the 2008 campaign - Harris, Heather E.; Moffitt, Kimberly R.; Squires, Catherine R., 1972- (Albany : State University of New York Press, 2010)
Annotation The editors place Barack Obama's presidential candidacy & 2008 victory in the context of the American experience with race & the media.
The Feminist Hero versus the BlackMessiah: Contesting Gender and Race in the 2008 Democratic Primary Epilogue; List of Contributors; Index.
Includes bibliographical references and index.
JSTOR
Keywords: Obama, Barack -- Influence; Obama, Barack; Political campaigns -- United States; Presidents -- United States -- Election -- 2008.; Race relations in mass media; United States -- Race relations -- Political aspects; Relations raciales dans les médias.; États-Unis -- Relations raciales -- Aspect politique; African American Studies; Ethnic Studies; SOCIAL SCIENCE; Influence (Literary, artistic, etc.); Political campaigns; Presidents -- Election; Race relations in mass media; Race relations -- Political aspects; United States; 2008; Electronic books